2011
DOI: 10.1038/onc.2011.484
|View full text |Cite
|
Sign up to set email alerts
|

Smad3 regulates E-cadherin via miRNA-200 pathway

Abstract: To identify potential microRNA (miRNA) links between Smad3, a mediator of TGF-b (transforming growth factor-b) signaling, and E-cadherin, we characterized the miRNA profiles of two gastric cancer cell lines: SNU484-LPCX, which does not express Smad3, and SNU484-Smad3, in which Smad3 is overexpressed. We found that among differentially expressed miRNAs, miR-200 family members are overexpressed in SNU484-Smad3 cells. Subsequent studies, including analysis of the effects of silencing Smad3 in SNU484-Smad3 cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 43 publications
2
75
1
Order By: Relevance
“…We further showed an inverse correlation between miR-200b-5p expression and mRNA expression of its target genes ZEB1, ZEB2, GATA2, and KDR in gingival tissue biopsies from periodontal disease patients, with ZEB2 and GATA2 being statistically significant and ZEB1 and KDR approaching a substantial trend toward significance. Previous studies have demonstrated that miRNA-200b interacts directly with the 3′ UTR of these genes and regulates their expression at the translational level (Ahn et al 2012). The above genes play central roles in pathways involved in re-epithelialization of gingival wounds (Tomikawa et al 2012), which is an important process in periodontal regeneration and reestablishment of tissue integrity, affecting treatment outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We further showed an inverse correlation between miR-200b-5p expression and mRNA expression of its target genes ZEB1, ZEB2, GATA2, and KDR in gingival tissue biopsies from periodontal disease patients, with ZEB2 and GATA2 being statistically significant and ZEB1 and KDR approaching a substantial trend toward significance. Previous studies have demonstrated that miRNA-200b interacts directly with the 3′ UTR of these genes and regulates their expression at the translational level (Ahn et al 2012). The above genes play central roles in pathways involved in re-epithelialization of gingival wounds (Tomikawa et al 2012), which is an important process in periodontal regeneration and reestablishment of tissue integrity, affecting treatment outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The "shortlisted" miR-200b gene targets were ZEB1, ZEB2, CDH1, GATA2, PLCG1, KDR, and UBC (normalization control), as well as SMAD3, which has been reported to regulate miR-200b (Ahn et al 2012). …”
Section: Qrt-pcr Analysis Of Mir-200b Gene Targets Expressionmentioning
confidence: 99%
“…Furthermore, the decreased FOG2 transcript expression in glomeruli from human subjects with DN suggests that the proposed miR-200-FOG2-Akt pathway may be significant not only in experimental animal models but also in human diabetic kidney disease as well. (47). In addition, our previous results have shown that miR-192 induced by TGF-␤ can target and down-regulate Zeb1/2 (E-box repressors) and thereby enhance the expression of miR-200b/c probably through E-boxes in their promoters (27).…”
Section: Discussionmentioning
confidence: 99%
“…4A and supplemental Table S1, p Ͻ 0.01), whereas Pin1 was higher in these cases (Fig. 4B and supplemental Table S1, p Ͻ 0.01) com- (30,31). We then used siRNA to knock down the expression of PEA3 and ELK-1 and found that knockdown of PEA3 decreased and knockdown of ELK-1 increased the expression of miRNA-200b (Fig.…”
Section: Decreased Mirna-200b and Increased Pin1 Expression In Human mentioning
confidence: 99%